Klasyfikacja krajów Unii Europejskiej a szybkość ich konwergencji dochodowej - Batóg, Barbara; Batóg, Jacek (Classification of the European Union Countries and the Rate Income Convergence, 2007)
The paper deals with income convergence in European Union countries. The main goals of the research were investigation of presence of different types of convergences among European countries and assessment of differences in the pattern of convergence for homogenous groups of countries. The partition of countries was based on two different criteria: first - the date of European Union access and second - an initial level of real PKB per capita. It turn out that income convergence is stronger and faster in case of the classification made according to the latter case.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 507-514